“LEVEL OF AWARENESS ABOUT THALASSEMIA AMONG FUTURE HEALTH CARE PROVIDERS” - Muhammad Saleem1 , Muhammad Bilal Ghafoor2 , Faheem Ahmed Memon3 , Zahid Mehmood4 , Sajida Khalid5 , Raghib Iqbal6 ., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2021)
ABSTRACT INTRODUCTION: Thalassemia is an autosomal recessive disorder of red blood cells. In Pakistan, thalassemia is one of the serious health problems with gene frequency about 5-8% resulting in approximately 9 million carriers of beta thalassemia responsible for 5000-6000 yearly birth of transfusion dependent thalassemia. The acquaintance about thalassemia is very inadequate amongst the public in developing nations. OBJECTIVE: To determine the level of awareness about thalassemia among future health care providers in Sheikh Zayed Medical College/Hospital Rahim Yar Khan (R.Y.K). METHODOLOGY: STUDY POPULATION: This research was performed in imminent health care workers in the district Rahim Yar Khan’s tertiary care hospital. STUDY TYPE: Cross sectional survey based study, with random purposive sampling technique. METHOD: A pre-designed survey form which comprises of altogether data about name, age, gender of contributors and questions about thalassemia was distributed among future health care providers including MBBS, Nursing and students of B.Sc. allied health sciences to evaluate awareness level. A total 13 questions were inquired to evaluate the level of knowledge about thalassemia. The knowledge level was determined by splitting the answers in three sets viz. contributors who gave less than six correct answers were believed as holding poor knowledge, who gave six to ten correct answers were believed as holding average knowledge and those who gave answers more than ten to thirteen were believed as holding good knowledge. RESULTS: Out of 400 subjects 294(73.5%) subjects have good knowledge of thalassemia, 92(23.0%) have an average knowledge about thalassemia however just 14(3.5%) have poor knowledge regarding thalassemia. CONCLUSION: In the future health care providers there is enough knowledge regarding thalassemia hence they can tackle this preposterous entity with full heart and help to make a thalassemia free Pakistan.